2005
DOI: 10.1080/00016480510026250
|View full text |Cite
|
Sign up to set email alerts
|

Functional studies of the human auditory pathway after monaural stimulation with pure tones. Establishing a normal database

Abstract: After delivering pure tones there was bilateral cortical activation in Brodmann areas 39 and 40, regardless of which ear was stimulated. Despite marked hyperperfusion in both areas 39, a more intense response was seen on the left compared to the right side, although this was not statistically significant. There was also activation in the executive frontal cortex areas 9 and 10 as well as in the temporal Brodmann areas 21 and 22. Simultaneously, area 38 of the temporal lobe was deactivated. In the subcortical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…This interaction would be useful when there are contradictory visual and vestibular inputs, since it allows a potential mismatch between two incongruent or misleading sensory inputs to be suppressed by shifting the sensory weight to the dominant or more reliable modality. Cortical deactivation during sensory stimulation has also been reported in the auditory system [19], suggesting the involvement of a number of both excitatory and inhibitory modulation and association relays, which might be common to various sensory systems.…”
Section: Discussionmentioning
confidence: 97%
“…This interaction would be useful when there are contradictory visual and vestibular inputs, since it allows a potential mismatch between two incongruent or misleading sensory inputs to be suppressed by shifting the sensory weight to the dominant or more reliable modality. Cortical deactivation during sensory stimulation has also been reported in the auditory system [19], suggesting the involvement of a number of both excitatory and inhibitory modulation and association relays, which might be common to various sensory systems.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, SPECT studies using white noise stimulation in patients with cochlear implants have shown increased regional blood flow to be greater on the side contralateral to the implant than on the ipsilateral side [10]. The results of our previous study [1] were supportive of the bilaterality of activation. However, our current study suggests that while activation is bilateral, there is seemingly no preference for stimulation of the contralateral side of the stimulated ear.…”
Section: Discussionmentioning
confidence: 66%
“…Clinical observations of functional asymmetries in the auditory system according to which ear is stimulated have been reported by Jerger [1] and Sininger and ConeWesson [18]. In addition, the existence of a 'leading ear' has been suggested by Tomatis [19], and the concepts of 'earedness' [20] and 'preferred ear' have also been reported.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations